PERANAN SYAHBANDAR DALAM MENUNJANG KESELAMATAN PELAYARAN DI KESYAHBANDARAN DAN OTORITAS PELABUHAN TELUK BAYUR - Diap Rianto Efendi dan Meita Lefi Kurnia (Fakultas Hukum Universitas Tamansiswa Padang, 2019)
Article 208 of Law Number 17 of 2008 concerning Shipping Syahbandar has the authority to coordinate all governmental activities at the port, inspect and store ship documents, documents, and ship reports, issue approval for vessel activities at the port, conduct ship inspections, issue Sailing Approval letters, conduct inspections a shipwreck, detained a ship by court order and carried out the crew's shipbuilding. The research results of the Syahbandar Role in supporting the safety of shipping at the Kesyahbandran and the Bayur Bay Port authority play an important role, Syahbandar has the highest authority in coordinating the activities of taboo, immigration, quarantine, and other activities of government institutions from its authority in examining, storing, publishing documents needed sea ​​transportation (ship) so that they can sail. such as ship-worthy certificates, sailing approval letters, anchored approval letters, cargo certificates, and entry and exit permits from the port. Constraints faced are still limited supporting infrastructure in the field, lack of human resources and lack of legal awareness. How to overcome the obstacles faced are efforts to meet supporting infrastructure in the field, additional human resources and the existence of legal awareness from users marine accounting to support the implementation of shahbandar duties.